Ethics in science and engineering - Speight, James G.; Foote, Russell, 1955- (Hoboken, N.J. : Wiley ; Salem, Mass. : Scrivener, 2011)
"For engineering and scientific endeavors to progress there must be generally accepted ethical guidelines in place to which engineers and scientists must adhere. This book explores the various scientific and engineering disciplines, examining the potential for unethical behavior by professionals. Documented examples are presented to show where unethical behavior could have been halted before it became an issue. The authors also look to the future to see what is in store for professionals in the scientific and engineering disciplines and how the potential for unethical behavior can be negated"--
"This book explores the various scientific and engineering disciplines, examining the potential for unethical behavior by professionals. Documented examples are presented to show where unethical behavior could have been halted before it became an issue. The authors also look to the future to see what is in store for professionals in the scientific and engineering disciplines and how the potential for unethical behavior can be negated"--
Explaining ethics -- Scientists and engineers -- The psychology and philosophy of ethics -- Education of scientists and engineers -- Scientific and engineering societies -- Codes of ethics and ethical studies -- Integrity in research -- Publication and communication -- Enforcement of codes and ethics.
Includes bibliographical references and index.
Keywords: Scientists -- Professional ethics; Engineers -- Professional ethics